iSearch-Enterprise Search Solution (International Journal of Engineering and Computer Science, 2015)
iSearch (Intelligent Search) is an enterprise search solution developed using Apache SOLR. iSearch system index data and documents from a variety of sources such as: file systems, intranets and document management systems. As the data in enterprise is becoming massive so iSearch  helps people to seek the specific  information they need of any rich text file format from anywhere inside their company.  iSearch identifies  and enables specific content across the enterprise to be  efficiently searched, and displayed only to authorized users.